2016
DOI: 10.1063/1.4954203
|View full text |Cite
|
Sign up to set email alerts
|

Contributed Review: Experimental characterization of inverse piezoelectric strain in GaN HEMTs via micro-Raman spectroscopy

Abstract: Micro-Raman thermography is one of the most popular techniques for measuring local temperature rise in gallium nitride (GaN) high electron mobility transistors (HEMTs) with high spatial and temporal resolution. However, accurate temperature measurements based on changes in the Stokes peak positions of the GaN epitaxial layers requires properly accounting for the stress and/or strain induced by the inverse piezoelectric effect. It is common practice to use the pinched OFF state as the unpowered reference for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 60 publications
(188 reference statements)
0
24
0
Order By: Relevance
“…The strain induced by the IPE effect changes the interatomic distances and force constants, resulting in changes in the optical phonon frequencies of the crystal. By probing the optical phonon frequencies near the Γ-point, micro-Raman spectroscopy can be used to experimentally measure this IPE-induced strain in GaN HEMTs with ≈1 µm spatial resolution from changes in the Raman peak positions [8]- [10].…”
Section: Fig 2 (A) Wurtzitementioning
confidence: 99%
See 4 more Smart Citations
“…The strain induced by the IPE effect changes the interatomic distances and force constants, resulting in changes in the optical phonon frequencies of the crystal. By probing the optical phonon frequencies near the Γ-point, micro-Raman spectroscopy can be used to experimentally measure this IPE-induced strain in GaN HEMTs with ≈1 µm spatial resolution from changes in the Raman peak positions [8]- [10].…”
Section: Fig 2 (A) Wurtzitementioning
confidence: 99%
“…Several hypotheses, such as uncertainties in the piezoelectric properties or phonon deformation potentials of GaN, have been suggested to explain the significant disagreement between measured and modeled values of strain, stress, and electric field [8]- [10], [11]. Our recent review [10] investigated many of these hypotheses in detail and concluded that none of them can satisfactorily resolve this disagreement.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations